Peran Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan di Era Digital - Ahmad Turmuzi (Syntax Corporation Indonesia, 2023)
Education in the digital era requires a strategic role of school principals in utilizing technology to improve the quality of learning. The purpose of this study is to analyze the role of school principals in improving the quality of education in the digital era. This research uses qualitative research methods. Data collection techniques in this study were carried out by literature study through exploration of journals, books and other information relevant to the research. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that principals have an important role in improving the quality of education in the digital era. The principal's role includes the ability to lead and manage the school well in order to optimally utilize digital technology, the ability to be an educator for teachers and school staff in order to develop their competence in utilizing digital technology and the ability to manage school resources, including digital technology, so that they can be used effectively and efficiently.